The Road to Hell: Neutralization of Killing in War. Issue 7 (2nd July 2016) - Kooistra, Paul G.; Mahoney, John S.
ABSTRACT: We explore how societies convince citizens to "go to hell, " where they kill strangers and risk their own lives. Our premise is that killing is difficult for most, regardless of context and widely considered a form of extreme deviance. Using Sykes and Matza's techniques of neutralization, we show how this aversion to killing is neutralized by placing individuals in organized—both macro-level bureaucratic and micro-level small primary groups—to justify killing. Consequently, the neutralization of mass killing illustrates the role of power in defining deviance, and the failure of neutralizations may sometimes explain Post-Traumatic Stress Disorder.